2008
DOI: 10.1007/s00213-008-1239-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of chronic antidepressant treatment on shuttle box escape deficits induced by uncontrollable stress

Abstract: Rationale-The transient behavioral deficit produced in rodents by typical learned helplessness (LH) procedures limits the utility of LH in identifying the therapeutic mechanisms associated with chronic antidepressant administration. In addition, LH procedures do not differentiate between different antidepressant classes as observed in the forced swim test.Objectives-To produce both a long lasting and antidepressant reversible behavioral deficit in a modified LH procedure that administers inescapable shock (IS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
1
18
0
12
Order By: Relevance
“…The helpless condition characterizes a depressive-like phenotype with changes in animal behavior that simulate the symptomatology of major depression patients (Dess et al 1988;Greenberg et al 1989;Adrien et al 1991). Chronic and acute treatment with several classes of antidepressants prevents or reverses this depressive-like behavior (Telner et al 1981;Sherman et al 1982;Martin et al 1987;Takamori et al 2001;Chourbaji et al 2005;Joca et al 2006;Valentine et al 2008;Zazpe et al 2007). …”
Section: Introductionmentioning
confidence: 97%
“…The helpless condition characterizes a depressive-like phenotype with changes in animal behavior that simulate the symptomatology of major depression patients (Dess et al 1988;Greenberg et al 1989;Adrien et al 1991). Chronic and acute treatment with several classes of antidepressants prevents or reverses this depressive-like behavior (Telner et al 1981;Sherman et al 1982;Martin et al 1987;Takamori et al 2001;Chourbaji et al 2005;Joca et al 2006;Valentine et al 2008;Zazpe et al 2007). …”
Section: Introductionmentioning
confidence: 97%
“…Previous studies reported that the helpless period lasted at least 10 days (Chourbaji et al 2005) and up to 21 days (Valentine et al 2008) depending on the protocol used. In our experiment, we noticed that animals exposed to a shock reminder presented a high and stable behavioural deficit 24 h after training until the final escape test, compared to animals with no reminder.…”
Section: Discussionmentioning
confidence: 98%
“…Electroconvulsive shocks (Dorworth & Overmier, 1977) and select drugs (e.g., desmethylimipramine; Leshner, Remler, Biegon, & Samuel, 1979) have also been shown to disrupt the interference produced by uncontrollable shock. Of translational importance, releasing learned helplessness animals from their deficits has been widely used as a criterion for testing the efficacy of anti-depressive drugs (e.g., Reed, Happe, Petty, & Bylund, 2008;Reed et al, 2009;Valentine, Dow, Banasr, Pittman, & Duman, 2008).…”
Section: Overmier Maier and Seligman's Helpless Dogsmentioning
confidence: 99%